Pengaruh Fasilitas Dan Digital Marketing Terhadap Peningkatan Jumlah Konsumen Pada Hotel Four Point By Sheraton Medan - Hasibuan, Anisa Falihah; Sahputra, Ngatno; Firah, Al (Universitas Dharmawangsa, 2025)
The purpose of this study was to determine the effect of facilities and digital marketing on increasing the number of consumers at the Four Points by Sheraton Medan Hotel. Data collection techniques used questionnaires, observations and literature with quantitative research methods and a sample size of 76 who were hotel consumers. The results of the study showed the effect of facilities on increasing the number of consumers, obtained a value of variable X1 of t count 3.293 ˃ t table 1.66571 meaning H1 is accepted and Ho is rejected. The digital marketing hypothesis test on increasing the number of consumers, obtained a value of variable X2 of t count 2.888 ˃ from t table 1.66023 meaning H2 is accepted and Ho is rejected. The significant value shows that it is smaller than alpha (0.004 ≤0.05) this means that it is significant so H3 is accepted and Ho is rejected. The Fcount value> Ftable (13.127≥3.12) then accepts H3 and rejects H0. This shows that together the independent variables have a significant effect on the dependent variable. The result of the determination coefficient analysis is 0.514. This result means that the magnitude of the independent variable affects the dependent variable by 51.4% while the remaining 48.6% is influenced by other factors outside the study.